Comparison of Methods for the Estimation of the Maximum Oxygen Uptake of Men Drug Addicts - Wang, Kun; Jiang, Haonan; Zhang, Tingran; Yin, Lian; Chen, Xi; Luo, Jiong (Frontiers in Physiology, 2021)
Background: Maximum oxygen uptake (VO2max) is an important respiratory physiological index of the aerobic endurance of the body, especially for special groups such as drug addicts, and it is an important indicator for assessing the cardiopulmonary function and formulating exercise prescriptions. Although the cardiopulmonary exercise test (CPX) is a classic method to directly measure VO2max, this method is limited by factors such as cumbersome operating procedures and expensive equipment, resulting in its relatively low applicability. Recently, many studies have begun to focus on the estimation of VO2max in different groups of people, but few studies have focused on drug addicts. Methods: Fifteen chemically synthesized drug addicts (such as amphetamines) and Fifteen plant-derived drug addicts (such as heroin) were recruited at the Chongqing Compulsory Isolation and Drug Rehabilitation Center in China. First, the VO2max of subjects was directly measured through the CPX. Second, after subjects were fully rested, they were required to complete the 30-s high-leg raise, 1,000-m walk, and 3-min step experiment. Finally, SPSS 21.0 software was used to perform the correlation and linear regression analysis to verify the estimated effectiveness. Results: (1) Regardless of chemically synthesized or natural plant-derived drug addicts, the years of drug use and walking time of 1,000 m were significantly negatively correlated with VO2max (chemically synthesized: P < 0.01 and natural plant-derived: P < 0.05), the number of 30-s high-leg raises was a significantly positive correlation with VO2max (P < 0.05 and P < 0.01), and the 3-min step index was significantly positively correlated with VO2max (P < 0.01 and P < 0.01). (2) Regression analysis shows that the 30-s high-leg lift, 1,000-m walking, and 3-min step experiment could effectively estimate the VO2max of chemically synthesized and natural plant-derived drug addicts. (3) Multiple linear regression constructed by the years of drug use combined with the step index has the highest estimated accuracy for the VO2max of chemically synthesized drug addicts (96.48%), while the unary regression equation established by a single step index has the highest prediction accuracy for the VO2max of natural plant-derived addicts (94.30%). Conclusion: The indirect measurement method could effectively estimate the VO2max of drug addicts, but different measurement methods have certain differences in the estimation accuracy of VO2max of different drug addicts. In the future, the physical characteristics of drug users can be fully considered, combined with more cutting-edge science and technology, to make the estimation accuracy of VO2max closer to the real level.